FEATURES OF THE SYMPTOM COMPLEX AND HEMODYNAMIC PARAMETERS IN PATIENTS WITH ISCHEMIC HEART DISEASE COMBINED WITH ARTERIAL HYPERTENSION - Zharylkasynova, G.; Narziev, L. (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The clinical and functional characteristics of the symptom complex and systemic hemodynamic parameters were investigated in 120 patients with ischemic heart disease combined with arterial hypertension. A predominance of anginal syndrome and dyspnea was identified, along with a high frequency of asthenic manifestations. More than 46% of patients experienced frequent angina attacks accompanied by pronounced hemodynamic disturbances. Gender- and age-related features were also observed, including a more pronounced clinical manifestation in middle-aged women.